The complete life cycle of a Cretaceous beetle parasitoid - Batelka, Jan; Engel, Michael S; Prokop, Jakub (Current biology, 2021)
Life cycles of parasites, particularly those with complex life histories and developmental pathways, are rarely preserved as fossils in total.1 The evidence is almost universally biased toward incomplete perspectives derived from a single sex or life stage.2,3 Here, we report a piece of Cretaceous Burmese amber that contains 28 males, a larviform female, and two longipede larvae of the wedge-shaped beetle Paleoripiphorus, and its potential cockroach host. Collectively, this fossil represents the complete series of free-living stages (except of the last larval instar) for a 99-million-year-old parasitoid insect from Myanmar (Figure 1 and Supplemental Information). The wedge-shaped beetles (Ripiphoridae) are of special interest among parasitoids because of their obligatory, protelean development in larvae of cockroaches, beetles, bees and wasps.4.
Keywords: Animals; Female; Amber; Coleoptera; ženské pohlaví; brouci; jantar; Myanmar; Male; hmyz; Fossils; zkameněliny; švábi; Larva; zvířata; mužské pohlaví; Cockroaches; Insecta; larva